The Incantation against Snakebite from Norov’s Psalmbook – Linguistic and Historical Aspects - Saldzhiev, Hristo (Studia Ceranea, 2024)
The paper explores the linguistic and cultural patterns behind an oral incantation against snakebite that appears on the last page of a Middle Bulgarian book of psalms. The manuscript dates back to the 14th century, and was created in the Eastern regions of Medieval Bulgaria, observing the orthography of the Tarnovo Literary traditions. The Russian traveller Norov found the book of psalms during a trip to the Holy Land at the beginning of the 19th century and brought it to Russia. The incantation contains a significant number of words of unclear origin. Yatsimirskiy – the first researcher of this incantation – offers two possible explanations about the source language that allude either to its derivation from an Oriental tongue, or to local folklore practices. Modern Russian researchers maintain the hypothesis about its folklore origin and emphasise its opening words sarandara/marandara as an example of ritual nonsense speech – in their view, this could have been a popular phenomenon in the ethnic religious practices of Slavic communities. After a linguistic analysis of the text and its unclear words, I hypothesise that the words belong to one of a range at used the incantation.